2014
DOI: 10.1136/annrheumdis-2013-204273
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between structural joint damage and urate deposition in gout: a plain radiography and dual-energy CT study

Abstract: MSU crystals are frequently present in joints affected by radiographic damage in gout. These findings support the concept that MSU crystals interact with articular tissues to influence the development of structural joint damage in this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
64
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 24 publications
4
64
0
3
Order By: Relevance
“…Two readers, blinded to the clinical variables and plain radiographic scores, evaluated the DECT scans for the presence and volumes of MSU crystal, independently. MSU crystal was considered present at each site only if reported by both readers and the average volume of MSU crystal was calculated [23]. …”
Section: Methodsmentioning
confidence: 99%
“…Two readers, blinded to the clinical variables and plain radiographic scores, evaluated the DECT scans for the presence and volumes of MSU crystal, independently. MSU crystal was considered present at each site only if reported by both readers and the average volume of MSU crystal was calculated [23]. …”
Section: Methodsmentioning
confidence: 99%
“…CT has shown that joints with intraosseous tophus are more likely to have features of abnormal new bone formation such as bony spurs, osteophytes, periosteal new bone formation, ankyloses and sclerosis [46]. In DECT studies, MSU crystals are frequently present in joints affected by radiographic damage in gout [47].…”
Section: Structural Consequences Of Tophaceous Goutmentioning
confidence: 98%
“…After presentation of the first gout flare, further flares frequently occur,20 and in the presence of untreated hyperuricaemia, these flares become more frequent, prolonged and polyarticular over time. In addition to the recurrent acute inflammatory flares, chronic gouty arthritis and gouty tophi may also develop, with risk of bone and joint damage 21. By contrast with the acute gout flares, gouty tophi are frequently painless without clinically apparent inflammation.…”
mentioning
confidence: 99%